INVESTIGATION OF MORAL DECISION-MAKING ATTITUDES OF YOUTH ATHLETES - Nurullah Emir Ekinci; Piyami Çakto; Ümmühan Tınaz; Büşra Işık; Alican Bayram (Sport şi Societate)
This study aims to examine the moral decision-making attitudes of youth athletes based on various variables. The population of the study consists of amateur sports clubs in the Kütahya province, while the sample was determined through snowball sampling, a non-probability sampling method (N=520, 104 males, 416 females). This is a quantitative research adopting a survey model. The “Moral Decision-Making Attitudes in Youth Sports Scale,” developed by Lee et al.,(2007) and adapted into Turkish by Gürpınar (2014), was used as the data collection tool. Reliability (Cronbach's Alpha), independent sample t-test, and one-way ANOVA were applied to the data. Tukey’s Post Hoc test was used as a second-level test. According to the significance level of P ≤ 0.05, participants' moral decision-making attitudes were found to be statistically significant based on gender, type of sport, and economic status, while no significant differences were found based on being a licensed athlete, being a national athlete, or place of residence. As a result, it was observed that being a licensed or national athlete does not significantly contribute to moral decision-making, whereas the type of sport played plays an important role in moral decision-making. This suggests that, especially in individual sports, it is crucial for coaches to prioritize instilling moral values in athletes before focusing on success.